School and individual-level correlates of physical activity in children: a multilevel approach - Marcos Britto Correa; Kelly Cordeira; Margarete Marques; Marlos Domingues; Flávio Demarco; Pedro Hallal (Revista Brasileira de Atividade Física e Saúde)
This study aimed to assess the association between individual and school environment variables and physical activity levels in Brazilian schoolchildren with 8-12 years of age.  A sample of children from 20 private and public schools (n=1,210) was selected. Total and leisure-time physical activities and active transportation to school (AT) were measured using a self-report instrument. Total and leisure-time physical inactivity (PI) were defined as